2020
DOI: 10.1051/sicotj/2020004
|View full text |Cite
|
Sign up to set email alerts
|

Does a fluoro-assisted direct anterior approach for total hip arthroplasty pose an excessive risk of radiation exposure to the surgeon?

Abstract: Introduction: Intraoperative fluoroscopy can be easily used because patients are placed in the supine position during total hip arthroplasty via direct anterior approach (DAA-THA) to reduce complications. However, the cumulative level of radiation exposure by intraoperative fluoroscopy increases as the annual number of cases increases, increasing the risk of influencing the health of both the patients and medical workers. The objective of the study was to compare the radiation exposure time of DAA-THA with ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Fluoroscopy is often used in orthopedic surgery, even for common fracture surgery, and radiation exposure is an unavoidable problem for orthopedic surgeons and staff. Jinnai et al reported significantly shorter fluoroscopy time and lower radiation exposure level for DAA-THA compared to proximal femur fractures [ 16 ]. In a recent systematic review, it was also reported that radiation exposure level during anterior THA is low and does not affect the surgeon or patient [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy is often used in orthopedic surgery, even for common fracture surgery, and radiation exposure is an unavoidable problem for orthopedic surgeons and staff. Jinnai et al reported significantly shorter fluoroscopy time and lower radiation exposure level for DAA-THA compared to proximal femur fractures [ 16 ]. In a recent systematic review, it was also reported that radiation exposure level during anterior THA is low and does not affect the surgeon or patient [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some uncommon complications that are still to be taken into account; Hogerzeil et al [ 6 ] reported the case of a 69-year-old male patient who developed acute compartment syndrome of the thigh after elective DAA THA while using therapeutic low molecular weight heparin as bridging for regular oral anticoagulation. Also the risk of excessive radiation exposure to both the patients and the surgeons has to be considered; Jinnai et al [ 54 ] compared the intraoperative fluoroscopy time of DAA-THA with that of osteosynthesis for proximal femoral fracture to determine if the level of radiation exposure exceeded safety limits and concluding that the intraoperative exposure level was significantly lower and the fluoroscopy time was significantly shorter in DAA-THA than in osteosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A traction table has several advantages such as traction of the lower limb enabling acetabular operation, ease of retention of the limb position for femoral operation, and prevention of intraoperative fracture during reduction [21]. In addition, health damage due to the exposure time becomes problematic for both patients and operators as the number of patients increases [22]. In general, the uoroscopy time required for the reduction procedure and internal xation is long in osteosynthesis of unstable femoral trochanteric fractures, and a similar tendency was noted in this study.…”
Section: Discussionmentioning
confidence: 99%